Community Involvement and the Use of Coffee Exocarp as a Growth Medium for Cajuput Plantation in Post-Mining Land Reclamation in PT Bukit Asam Tbk (PTBA) - Putra, Taupan Ariansyah; Amin Rejo; Yuanita Windusari (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
The cajuput plant (Melaleuca cajuputi) is valued for its essential oil production and its ability to thrive in challenging environments, including post-mining lands. PT Bukit Asam Tbk (PTBA) has cultivated this plant extensively to supply seeds for reclamation projects on former mine sites, along with the provision of location-specific fertilizers. This study aims to identify the new alternative organic materials, determining the optimal formula for plant growth media and also to measure the tangible and intangible impacts of the community involvement. Following the implementation of statistical testing involving the analysis of variance model (ANOVA) and subsequent test, which is the least significant difference (LSD) test, definitive findings reveal that incorporating coffee exocarp as a growth medium significantly impacts the elevation of plant height and the augmentation of Cajuput leaf count. The most efficacious treatment is delineated as P2, characterized by a 1:1 composition of coffee exocarp and soil. The involvement of the local community has precipitated several advantageous outcomes, encompassing the creation of employment opportunities, the facilitation of economic equilibrium, and the development of smallholder forestry enterprises within the local community.